Serbia and Montenegro : An Agenda for Economic Growth and Employment - World Bank (Washington, DC, 2013)
Upon resumption of its transition to a market economy in late-2000, Serbia made good initial progress across a range of areas. This progress began from a very difficult starting point which reflected the legacy of a decade of isolation, conflict, and poor economic management. However, deep structural weaknesses remain. Growth rates of around 4 percent per year will not suffice to produce a rapid convergence of living standards towards historical levels. Moreover, the positive elements of Serbia's recent performance are not sustainable without further adjustment and sustained reform. This report analyzes Serbia's recent performance and near-term reform priorities, in five areas which are particularly important for growth and employment creation. Eight themes emerge as the key reform priorities for enhancing growth and employment generation in Serbia: enhanced political stability and improved governance are key prerequisites for sustained growth; reduction of the public sector, thus reducing spending and fiscal burdens; promotion of export development, addressing the anti-export bias, through adequate institutional framework, tariff reform, and a strong trade policy; completion of enterprises and banks privatization; enhanced financial discipline and competitiveness; enabling an improved business environment; foster an enhanced, flexible formal labor market; enhance quality of, and access to education and training. The report demonstrates in great detail the outlined package of substantial and permanent fiscal adjustment, and sustained progress in structural reform, in order to generate the higher investment rates and a more competitive economy which can prod sustainable growth, and improved living standards over the medium-term. Such policies need to be implemented with urgency and unwavering commitment.